The students' brainwork intensification via the computer visualization of study materials - Halyna I. Ivanova; Olena O. Lavrentieva; Larysa F. Eivas; Iuliia O. Zenkovych; Aleksandr D. Uchitel (Academy of Cognitive and Natural Sciences, 2020)
The paper the approaches to the intensification of the students' brainwork by means of computer visualization of study material have been disclosed. In general, the content of students' brainwork has been presented as a type of activity providing the cognitive process, mastering the techniques and ways of thinking, developing the capabilities and abilities of the individual, the product of which is a certain form of information, as a result of the brainwork the outlook of the subject of work is enriched. It is shown the visualization is the process of presenting data in the form of an image with the aim of maximum ease of understanding; the giving process of visual form to any mental object. In the paper the content, techniques, methods and software for creating visualization tools for study material has exposed. The essence and computer tools for creating such types of visualization of educational material like mind maps, supporting notes and infographics have been illustrated; they have been concretized from the point of view of application in the course of studying the mathematical sciences. It is proved the use of visualization tools for study materials helps to increase the intensity and effectiveness of students' brainwork. Based on the results of an empirical study, it has been concluded the visualization of study materials contributes to the formation of students' key intellectual competencies and forming their brainwork culture.